2001
DOI: 10.1046/j.1570-7458.2001.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns of persistence and infectivity of Metarhizium anisopliae var. acridum in grasshopper cadavers in the Sahel

Abstract: Field‐based experiments were conducted to evaluate the fate and infectivity of the entomopathogenic fungus Metarhizium anisopliae var. acridum (Deuteromycotina: Hyphomycetes) in grasshopper cadavers in the Sahel. Unlike uninfected cadavers, which were rapidly scavenged, those infected with the fungus persisted in the environment for a number of weeks. The environmental factor most associated with cadaver disappearance was rainfall. The high environmental humidity associated with rainfall was also required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…Our results are in line with Marikovsky's field study showing that Formica rufa ants never feed on sporulating nestmates infected by Tarichium fungi [44]. Such an avoidance behaviour may explain why sporulating insects seem to remain in the environment for weeks while uninfected decaying prey are quickly eaten by a wide range of scavengers like birds or other invertebrates [45]. Put together, these results suggest that sporulating corpses are unattractive and even repellent to scavenging ants that refrain from retrieving such food items.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are in line with Marikovsky's field study showing that Formica rufa ants never feed on sporulating nestmates infected by Tarichium fungi [44]. Such an avoidance behaviour may explain why sporulating insects seem to remain in the environment for weeks while uninfected decaying prey are quickly eaten by a wide range of scavengers like birds or other invertebrates [45]. Put together, these results suggest that sporulating corpses are unattractive and even repellent to scavenging ants that refrain from retrieving such food items.…”
Section: Discussionsupporting
confidence: 89%
“…Luz et al (1999 also found that infected dead T. sordida and T. infestans disappeared due to the activity of ants and other animals. Arthurs et al (2001) noticed that uninfected grasshopper cadavers in the Niger Republic were rapidly scavenged largely by ground-dwelling ants and beetles, but those infected with the fungus persisted in the environment for a number of weeks, which was not found in our experiments.…”
Section: Discussioncontrasting
confidence: 71%
“…M. anisopliae conidia are primarily found in the top 1-5 cm of soil (Hu and St. Leger, 2002;Vänninen et al, 2000). Soil temperatures of up to 65°C have been reported during the rainy season in the Niger Republic, West Africa (Arthurs et al, 2001). We observed that soil surfaces subjected to full sunlight reached 60°C in irrigatedcorn Welds in Logan, UT USA (41°N) in mid-July at 5:00 pm (daylight saving time).…”
Section: Introductionmentioning
confidence: 64%